Communication Technologies for Vehicles 5th International Workshop, Nets4Cars/Nets4Trains 2013, Villeneuve d$1 (BAscq, France, May 14-15, 2013. Proceedings /s - Berbineau, Marion; Jonsson, Magnus; Bonnin, Jean-Marie.; Cherkaoui, Soumaya; Aguado, Marina; Rico-Garcia, Cristina; Ghannoum, Hassan; Mehmood, Rashid; Vinel, Alexey; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book constitutes the joint refereed proceedings of the 5th International Workshop on Communication Technologies for Vehicles/Trains, Nets4Cars 2013 and Nets4Trains 2013, held in Vilnius, Lithuania, in May 2013. The 12 full papers of the road track and 5 full papers of the rail track presented together with 3 invited talks were carefully reviewed and selected from 24 submissions. They address topics such as intra-vehicle, inter-vehicle and vehicle to infrastructure communications (protocols and standards), mobility and traffic models (models, methodologies, and techniques), testing, and applications.
Invited Papers -- V2V Communication Channels: State of Knowledge, New Results, and What$1 (Bs Next -- Internet Onboard: Technical Analysis -- A QoS-Based Multi-user Scheduler Applied to Railway Radio-Communications -- Road Track -- Survey on Context-Aware Publish/Subscribe Systems for VANET -- A Survey on Security in Vehicular Ad Hoc Networks -- Wireless Vehicular Network Standard Harmonization -- Multi-technology Vehicular Cooperative System Based on Software Defined Radio (SDR) -- Performance of Inter-Vehicle Relay Network Based IR-UWB -- The Effects of Increasing Antenna Arrays and Spatial Correlation on Loading Algorithm for Closed-Loop MIMO Vehicle-to-Infrastructure Communications -- Increased Communication Reliability for Delay-Sensitive Platooning Applications on Top of IEEE 802.11p -- Development of Car2X Communication and Localization PHY and MAC Protocol Following Iterative Spiral Model Using Simulation and Emulation -- Characterization of a Laser Scanner Sensor for the Use as a Reference System in Vehicular Relative Positioning -- Estimating the Scheduling Discipline of an Ethernet Switch Using Constant Bit-Rate Probes -- Bridging Physical and Digital Traffic System Simulations with the Gulliver Test-Bed -- Open-VSeSeMe: A Middleware for Efficient Vehicular Sensor Processing -- Rail Track -- LTE Based Communication System for Urban Guided-Transport: A QoS Performance Study -- Performance of LTE in High Speed Railway Scenarios -- Generating Test Scenarios Based on Real-World Traces for ERTMS Telecommunication Subsystem Evaluation -- Blind Digital Modulation Detector for MIMO Systems over High-Speed Railway Channels -- Enhancing the CATS Framework by Providing Asynchronous Deployment for Mobile Application.s
Keywords: Computer science; Computer Communication Networks; Software engineering; Computer system performance; Computer simulation; Computer Science; Computer Communication Networks; Special Purpose and Application-Based Systems; System Performance and Evaluation; Simulation and Modeling; Computer Science, general; Computer Science, general